Sofosbuvir Based Regimens in the Treatment of Chronic Hepatitis C with Compensated Liver Cirrhosis in Community Care Setting - Vijay Gayam; Amrendra Kumar Mandal; Mazin Khalid; Osama Mukhtar; Arshpal Gill; Pavani Garlapati; Mowyad Khalid; Mohammed Mansour (International Journal of Hepatology)
Background. Direct-acting antiviral (DAA) drugs have been highly effective in the treatment of chronic hepatitis C (CHC) infection. We aim to evaluate the treatment response of Sofosbuvir based DAA in CHC patients with compensated liver cirrhosis as limited data exists in the real-world community setting. Methods. All the CHC patients with compensated liver cirrhosis treated with Sofosbuvir based DAAs between January 2014 and December 2017 in a community clinic setting were retrospectively analyzed. Pretreatment baseline patient characteristics, treatment efficacy with the sustained virologic response at 12 weeks posttreatment (SVR12), and adverse reactions were assessed. Results. One hundred and twelve patients with CHC infection and concurrent compensated cirrhosis were included in the study. Black patients represented the majority of the study population (64%). Eighty-seven patients were treated with Ledipasvir/Sofosbuvir (LDV/SOF) ±Ribavirin and 25 patients were treated with Sofosbuvir/Velpatasvir (SOF/VEL). Overall, SVR 12 after treatment was achieved in 90% in patients who received one of the two DAA regimens (89.7% in LDV/SOF group and 92% in SOF/VEL group). SVR 12 did not vary based on age, sex, body mass index, baseline HCV viral load, HCV/HIV coinfection, type of genotype, and prior treatment status. Apart from a low platelet count, there were no other factors associated with a statistical difference in SVR 12(p=0.002) between the two regimens. Fatigue (35%) was the most common adverse effect and no patients discontinued treatment due to adverse effects. Conclusion. In the community care setting, Sofosbuvir based DAAs are safe, effective with high overall SVR, and well tolerated in patients with CHC patients with compensated liver cirrhosis.